Substantiation of additional diagnostic methods for mental and cognitive disorders in the structure of childhood absence epilepsy - V. A. Karlov; A. A. Dubrovskaya (Русский журнал детской неврологии)
Background. Childhood absence epilepsy (CAE) is a common form of epilepsy in preschool and primary school children, characterized by absences and pathognomonic electroencephalographic signs. The question regarding the characterization of intelligence remains relevant today – as available data are often contradictory.Aim. To analyse the data obtained during the study using age-matched questionnaires and tests, to assess the frequency of occurrence and clinical course of cognitive disorders and changes in the emotional-volitional sphere in patients with CAE.Materials and methods. A total 49 patients diagnosed with DAE were observed, divided into two groups according to age: 1) children 4–10 years old (n = 26); 2) children 11–17 years old (n = 23). 24 healthy children were included in the control group. The methods of assessment used were: test for preschoolers “Numbers”, Stroop test, graphic method of M.A. Panfilova “Cactus”, trail making test, WAM questionnaire (well-being, activity, mood), Eysenck questionnaire, and Achenbach questionnaire.Results. In group 1 of combined diagnostics compared to the control group there were statistically significant deviations in the study of short-term memory, flexibility of cognitive control and emotional sphere of the child. In group 2 of combined diagnostics higher levels of emotional instability, lower overall well-being, and reduced activity and mood scores were identified. The study of the peculiarities of behaviour deviating from the accepted social norm demonstrates that isolation, somatic problems, socialization disorders, attention problems and the index of internal problems are significantly higher in patients with CAE than in the healthy children.Conclusion. Children with CAE have a significant risk of developing psychopathologic manifestations compared to the general population. Children with CAE need timely additional diagnostics of higher mental functions, which in turn will improve adaptation to living conditions, education and quality of life.